Spatio-Temporal Systems in Shakespeare’s Dialogues: A Case from Julius Caesar - Nakayasu, Minako (Studia Anglica Posnaniensia, 2021)
This paper performs both quantitative and qualitative analyses of the spatio-temporal systems in Julius Caesar. First, a quantitative analysis of how frequently each element of space and time is employed shows which perspective, i.e., proximal or distal, is likely to be taken. Second, a qualitative analysis reveals how these elements are related with each other to take either proximal or distal perspective, and how these perspectives change in discourse. In these analyses, the present paper pays attention to the interactions between the interlocutors in order to investigate how these interactions in dialogues impact the selection of elements of space and time.